Respuesta :

Answer:

y = -1x - 3

Step-by-step explanation:

y = mx + b

m = slope = -1

b = y-intercept = -3

Plug in

y = -1x - 3

Answer:

y = -x - 1

Step-by-step explanation:

Slope - Intercept form is y = mx + b

m = slope

b = y-intercept

We already have the slope of -1.  Substitute it into the equation.

y = -x + b

To find b, substitute the given point (2, -3) into the equation.  

-3 = -2 + b

b = -1

Substitute the value of b into the equation and you are left with:

y = -x - 1

ACCESS MORE